THE ANALYSIS OF MAJOR GRAMMATICAL ERRORS IN STUDENTS’ WRITING - Paramita, Paulina Erawati (Jurnal Pendidikan Bahasa, 2016)
This study investigates and classifies grammatical errors in writing made by year nine students at SMP Gembala Baik Bilingual Class. The samples of this research were 30 students randomly selected from 61 students. Descriptive qualitative was used to describe the errors made by the 30 students. They were asked to write about their holidays, and then the analysis was conducted to see the errors found in their writings. The results show that There were three errors in  noun endings,  two errors in subject-verb agreement, four errors in  verb tense,  four errors in  verb form, eight errors in  capitalization,  six errors in  sentence fragment, and  two errors in  comma errors.  The information of the types of students’ errors can be used as a guidance to evaluate the weakness or progress of students’ ability in learning English, particularly in writing.Keywords: grammatical errors, error analysis, contrastive analysis, English  learning.